Soybean futures crush spread arbitrage: Trading strategies and market efficiency - John B. Mitchell (Journal of Risk and Financial Management, 2010)
This paper revisits the soybean crush spread arbitrage work of Simon (1999) by studying a longer time period, wider variety of entry and exit limits, and the risk-return relationship between entry and exit limits. The lengths of winning and losing trades are found to differ systematically, with winning trades significantly shorter on average than losing trades. Exiting trades near the 5- day moving average is shown to improve trade performance relative to a reversal of sign and magnitude from the entry spread. These results lead to trading rules designed to prevent lengthy trades; however, the profitability of trading rules is found to be unstable
Keywords: C13; 330; Futures; Spread; Arbitrage; Market Efficiency; Trading Strategies